Gambaran Diri Remaja di Desa Kaliboto Kecamatan Wonodadi Kabupaten Blitar - Sulistyorini, Ariani; Oktavia, Siska (Universitas Muhammadiyah Jember, 2023)
Background and Aim: Body-image is an individual's attitude toward feelings about body size and shape which consists of positive Body-image and negative self-image. Adolescence is a period of transition from childhood to adulthood. Body-image is one of the problems that often occurs in adolescents. One of the problems that occurs in adolescents is low Body-esteem caused by physical appearance. The aim of the study was to find out the Body-image of adolescents in Kaliboto Village, Wonodadi District, Blitar Regency. Methods: The research design used descriptive, the study population was all adolescents in Kaliboto Village, Wonodadi District, Blitar Regency, consisting of 146 respondents and a sample of 59 respondents using a purposive sampling technique. The research was carried out on February 22 - March 21 2022 with the research variable, namely the self-description of adolescents in Kaliboto Village, Wonodadi District, Blitar Regency, the research instrument used a questionnaire, data were analyzed in the frequency distribution table and interpreted quantitatively. Results: Of the 59 respondents, it was found that most of the respondents, namely 31 respondents (53%) had a negative body-image and almost half of the respondents, namely 28 respondents (48%) had a positive body-image. Body-image is caused by several factors, namely age, gender, education, where they live together, weight, height, feelings of shame about body shape, who are close friends and who they often communicate with. Conclusions: Educational institutions are expected to add references related to mental nursing care, especially regarding adolescent self-image. Respondents are expected to be able to increase their understanding of negative self-images by loving themselves and not comparing themselves with others so that they become positive body-images.